2016
DOI: 10.1016/j.mrgentox.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring reproducibility of dose response data for the Pig-a assay using covariate benchmark dose analysis

Abstract: The reproducibility of the in vivo Pig-a gene mutation test system was assessed across 13 different Japanese laboratories. In each laboratory rats were exposed to the same dosing regimen of N-nitroso-N-ethylurea (ENU), and red blood cells (RBCs) and reticulocytes (RETs) were collected for mutant phenotypic analysis using flow cytometry. Mutant frequency dose response data were analysed using the PROAST benchmark dose (BMD) statistical package. Laboratory was used as a covariate during the analysis to allow all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…In contrast, overlapping confidence intervals signify that any potency differences cannot be resolved on the basis of the available data (i.e., the true BMDs could be the same, or could differ). Critically, when the range delineated by all the confidence intervals examined is small enough to be considered as biologically or practically insignificant, it may be concluded that the potencies are sufficiently similar to consider the associated studies reproducible [Johnson et al, ; Wills et al, ,b].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, overlapping confidence intervals signify that any potency differences cannot be resolved on the basis of the available data (i.e., the true BMDs could be the same, or could differ). Critically, when the range delineated by all the confidence intervals examined is small enough to be considered as biologically or practically insignificant, it may be concluded that the potencies are sufficiently similar to consider the associated studies reproducible [Johnson et al, ; Wills et al, ,b].…”
Section: Resultsmentioning
confidence: 99%
“…This or other processing steps may contribute to the modest day‐to‐day variation observed in spontaneous Pig‐a mutant RBC frequencies for these studies. Variation among experiments both among and within laboratories has been observed and documented in studies of Pig‐a mutagenesis in rats though differences are considered modest and results are considered quite reproducible [Godin‐Ethier et al, ; Johnson et al, ]. Reducing such variation among rodent Pig‐a mutation assays, especially for spontaneous mutant frequencies, remains an active area of research and development.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the approach utilized by Johnson et al . (2016) for studying Japanese laboratory‐generated Pig‐a data, and takes advantage of the software's ability to analyze multiple dose responses at the same time using conserved shape parameters. This has been shown to improve the precision of BMD analyses (Slob and Setzer, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As described by the Guidance Document on the Validation and International Acceptance of New or Updated Methods for Hazard Assessment (Organization for Economic Cooperation and Development (OECD), 2005), this includes assessments of reproducibility. The authors of several intra‐ and inter‐laboratory Pig‐a trials have concluded that the reproducibility of erythrocyte‐based assays are high (Chung et al ., 2018; Dertinger et al ., 2011a; Kimoto et al ., 2013, 2016; Gollapudi et al ., 2015; Johnson et al ., 2016; Raschke et al ., 2016). That being said, not all of these data were generated using current state‐of‐the art scoring methods, or have been rigorously evaluated in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%